ANALISIS PENGARUH DANA PIHAK KETIGA DAN PENYALURAN DANA TERHADAP PROFITABILITAS BANK SYARIAH (STUDY KASUS PT. BANK SYARI’AH MANDIRI PERIODE 2001-2010) - Ervalina, Ratih Oktia (e-Journal Perdagangan Industri dan Moneter, 2013)
The purpose of this research is to determine the dominant influnce factors in Syariah Mandiri Bank profit. This research uses quantitative descriptive method through time series data to know the dominant influnce factors in Syariah Mandiri Bank profit. The result of this research shows the coefficient of independent variabe in which for third party fund is 1,820 and for fund distribution is 2,815. It means that the third party has a good influence towards Bank profit..